2015
DOI: 10.1080/19491034.2014.1003745
|View full text |Cite|
|
Sign up to set email alerts
|

Chromosome Conformation of Human Fibroblasts Grown in 3-Dimensional Spheroids

Abstract: In the study of interphase chromosome organization, genome-wide chromosome conformation capture (Hi-C) maps are often generated using 2-dimensional (2D) monolayer cultures. These 2D cells have morphological deviations from cells that exist in 3-dimensional (3D) tissues in vivo, and may not maintain the same chromosome conformation. We used Hi-C maps to test the extent of differences in chromosome conformation between human fibroblasts grown in 2D cultures and those grown in 3D spheroids. Significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…It has previously been shown that chromosome 18 had increased intra-chromosomal interactions while the chromosomes whose TADs changed the most, including 19, had decreased intrachromosomal interactions. 13 Additionally, chromosome 19 has the highest gene density while chromosome 18 has the lowest, which further suggests that gene expression and chromosomal structure are tightly coupled. Fig.…”
Section: Relationship Between Chromosome Conformation and Gene Expresmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that chromosome 18 had increased intra-chromosomal interactions while the chromosomes whose TADs changed the most, including 19, had decreased intrachromosomal interactions. 13 Additionally, chromosome 19 has the highest gene density while chromosome 18 has the lowest, which further suggests that gene expression and chromosomal structure are tightly coupled. Fig.…”
Section: Relationship Between Chromosome Conformation and Gene Expresmentioning
confidence: 99%
“…After 48-h of growth, we sampled the cells for Hi-C and RNA-seq analyses. Hi-C libraries were constructed from 20 million cells for each culturing condition as described by Chen et al 13 Briefly, we used the HindIII restriction enzyme (RE) for chromatin digestion. RE created DNA fragment ends were marked with biotin-dCTP (Cat# 19518-018, Life Technologies) and re-ligated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hi-C, RNA-seq, and FISH data were collected from human fibroblasts and HT-29 cell lines as described by Chen and colleagues (12). Cell culture in 2D and three dimensional (3D) growth was performed as described by Chen and colleagues (13). Extended protocols for RNA-seq, Hi-C, and FISH are mentioned in the Supplementary Methods.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…18) with official gene symbols and the default background set for human analysis. The statistical test comparing samples was performed as described by Chen and colleagues (13).…”
Section: Two-way Anovamentioning
confidence: 99%